Ensaio clínico randomizado controlado triplo cego para avaliação da ansiedade e estresse de crianças submetidas à sedação com midazolam oral durante tratamento odontológico - Gomes, Heloisa de Sousa (2013)
The fear and anxiety represent a barrier for dental care and can cause behavioral and physiological changes. These changes can be evaluated through behavioral scales and the measurement of salivary cortisol levels. The aim of this study was to evaluate the level of salivary cortisol in children during restorative dental treatment under moderate sedation with midazolam and taken a placebo and verify the correlation between this physiological measure and the assessment of the behavior conducted through the scale Ohio State University Behavioral Rating Scale (OSUBRS). A randomized controlled crossover triple-blind clinical trial was conducted with 18 healthy children from 2 to 5-year olds with necessity of at least two sessions of restorative dental treatment. Each child was undergo treatment under sedation with 1mg/kg oral midazolam in one session and the other with a placebo and in both sessions protective stabilization was associated. The assessment of child behavior was conducted from videos of clinical sessions using the scale of OSUBRS and the salivary cortisol level was evaluated in 4 moments on the two sessions (waking up, on arrival at the Dental School (DS), 25 minutes after the anesthesia and 25 minutes after finishing the procedure). The saliva samples were analyzed by the Enzyme Immunoassay test to get the mean salivary cortisol level. The results showed that the salivary cortisol level was lower when the children had received midazolam than when they had received the placebo at the moment of anesthesia (p=0.004). It was! Observed greater variation in cortisol level when the children received placebo than when they received midazolam. However, there were no differences between salivary cortisol levels observed in the four moments during treatment with sedation (p = 0.319) or placebo (p = 0.080). Regarding the child behavior it was not observed improvement during the treatment with sedation compared with placebo. The salivary cortisol levels showed no statistically significant correlation with the child’s behavior assessed by the scale OSUBRS during dental treatment under sedation or placebo. Therefore it was concluded that the oral midazolam dose of 1.0 mg/kg is effective in reducing the levels of salivary cortisol of children from 2 to 5-year olds during restorative dental treatment. However, this reduction in the level of cortisol in saliva did not reflect in better clinical behavior of these children.